Komposisi dan Kemelimpahan Fitoplankton di Telaga Menjer, Wonosobo. - Dyah Ayu Kumalasari; Tri Retnaningsih Soeprobowati; Sapto Purnomo Putro (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Phytoplankton are the dominant primary producers in aquatic ecosystems, Phytoplankton are sensitive to environment as changes. Therefore, the phytoplankton is often used for bioindicators of water quality. The purpose of this study was to obtain information on the abundance, diversity, evenness, and dominance of phytoplankton in Menjer Lake and examine the condition of the water quality and its effects on phytoplankton abundance. Research on the composition and abundance of phytoplankton in Menjer Lake was conducted in May 2015. Phytoplankton samples were taken using a plankton net size 25 µk and identification of phytoplankton using SRC and the microscope. The composition of phytoplankton in Menjer Lake consist of 40 species from six divisions in the following order: Bacillariophyte (17 species), Chlorophyte (15 species), Cyanophyte (3 species), Chrysophyte (1 species), Chryptophyte (1 species ) and Dinoflagellate (3 species). Phytoplankton abundance was highest at the net culture (11.884 ind/ l), then the abundance of phytoplankton low at the outlet station (8.476 ind/ l). The result of analysis on Phytoplankton diversity of stasions at Menjer lake the value 2,27-2,62 that means of high diversity. Uniformity index (e) at Menjer lake the value 0,84-0,92, that means the condition of phytoplankton community include into stable. Dominance index (D) was highest at the outlet station phytoplankton species to dominate Aulacoseira granulata was indicated of its water is eutrophic. Keywords: Menjer Lake, bioindicators, phytoplankton